Comparison of functional characteristics of distinct Saccharomyces boulardii strains isolated from commercial food supplements - Goktas, Hamza; Dertli, Enes; Sagdic, Osman (ELSEVIER, 2021)
Saccharomyces boulardii is a probiotic yeast with several health benefits. An important number of products are available in the market claiming to contain probiotic S. boulardii strains and these numbers are increasing. In this study, S. boulardii strains were isolated from commercial products, identified and characterised in terms of several probiotic features. Eleven distinct S. boulardii strains were identified by genotypic tests followed by FT-IR spectroscopy and biochemical analysis which were used to differentiate S. boulardii strains from other yeasts including Saccharomyces cerevisiae. All tested strains showed high level of survival under harsh conditions and auto-aggregation characteristics. The hydrophobicity of S. boulardii strains revealed strain specific features and only two strains survived at pH of 2.5. A high level of survival under bile salts conditions were observed for all tested strains. Distinct S. boulardii strains were found to be resistant to bacterial antibiotics whereas they were sensitive to fungal antibiotics. Finally, S. boulardii strains showed high level of antibacterial and antifungal activities particularly against Salmonella Typhimurium and Aspergillus niger, respectively. This study revealed the differences in the functional characteristics of S. boulardii strains available in the market.
Keywords: S. boulardii; Probiotic properties; FT-IR identification; Commercial food supplements; IN-VITRO; YEASTS; IDENTIFICATION; BACTERIA; TOOL; Food Science & Technology